A conceptual model for characterizing the problem domain. (October 2016) - Winters, Kirsten M.; Lach, Denise; Cushing, Judith B.
Defining characteristics of a problem domain continues to challenge developers of visualization software although it is essential for designing both tools and resulting visualizations. Additionally, effectiveness of a visualization software tool often depends on the context of systems and actors within the domain problem. The nested blocks and guidelines model is a useful template for informing design and evaluation criteria for visualization software development because it aligns design to need. Characterizing the outermost block of the nested model—the domain problem—is challenging, mainly due to the nature of contemporary domain problems, which are dynamic and by definition difficult to problematize. We offer here our emerging conceptual model, based on the central question in our research study—what visualization works for whom and in which situation—to characterize the outermost block, the domain problem, of the nested model. We apply examples from a 3-year case study of visualization software design and development to demonstrate how the conceptual model might be used to create evaluation criteria affecting design and development of a visualization tool.